PEMODELAN DAN SIMULASI DAFTAR ULANG PPDB PADA SEKOLAH MENENGAH ATAS DENGAN METODE MULTIPLE CHANNELS SINGLE PHASE (M/M/1) - Meizalina, Mutiara Amalia; Ermatita, Ermatita; Ibrahim, Ali (Universitas Lancang Kuning, 2024)
The New Student Admission (PPDB) process in high schools is complex and requires efficient management to avoid long queues and errors in data processing. Until now, the Re-registration of New Student Admissions in high schools has always involved hundreds of prospective students in one school, resulting in long service and waiting times. Therefore, a solution is needed to address these issues and optimize available resources. This study uses the Multi Channels Single Phase (M/M/c) method with the Multi Channels Multi Phase (M/M/s) method. Modeling and simulation can help identify factors affecting latency, service time, and the number of students that can be served within a specific period. This can assist schools in planning their student population and optimizing the use of available resources. Based on data analysis, discussion, and conclusions from the comparison of two Modeling and Queue Simulation Methods in the re-registration process of New Student Admissions at SMA Negeri 10 Palembang, namely the Multi Channel-Single Phase and Multi Channel-Multi Phase Methods.